Academic Fraud Behavior of Accounting Students in Dimensions of Fraud Hexagon Theory - Dian Oktarina; Nur Syahrur Ramadhan (JAFFA, 2023)
The purpose of this research is to show the fraud hexagon theory perspective on the occurrence of academic fraud for accounting students. The independent variable in this research is pressure, opportunities, rationalization, capability, arrogance and collusion while the dependent variable is academic fraud. This research uses primary data obtained from online questionnaires. The sample of this research uses accounting students who are registered at the University of Hayam Wuruk Perbanas. This research used multiple linear regression. The results of this study indicate that opportunities, capability and collusion have a positive effect, while the pressure, rationalization and arrogance have no effect on the occurrence of academic fraud